2015
DOI: 10.1155/2015/917806
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism Affects Vascularization and Promotes Immune Cells Infiltration into Pancreatic Islets of Female Rabbits

Abstract: Thyroidectomy induces pancreatic edema and immune cells infiltration similarly to that observed in pancreatitis. In spite of the controverted effects of hypothyroidism on serum glucose and insulin concentrations, the number and proliferation of Langerhans islet cells as well as the presence of extracellular matrix are affected depending on the islet size. In this study, we evaluated the effect of methimazole-induced hypothyroidism on the vascularization and immune cells infiltration into islets. A general obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
(56 reference statements)
0
7
1
Order By: Relevance
“…Although we did not find any difference in the averaged cross-sectional area of hepatocytes among groups, the moderate steatosis and the perisinusoidal fibrosis observed in hypothyroid rabbits could be enough to affect the hepatic vascularization [34]. Indeed, hypothyroidism modifies the blood vessels into pancreatic islets [19]. Contrary to a severe steatosis [35,36], the moderate steatosis induced by a short-time hypothyroidism in female rabbits allows the regeneration of the liver.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Although we did not find any difference in the averaged cross-sectional area of hepatocytes among groups, the moderate steatosis and the perisinusoidal fibrosis observed in hypothyroid rabbits could be enough to affect the hepatic vascularization [34]. Indeed, hypothyroidism modifies the blood vessels into pancreatic islets [19]. Contrary to a severe steatosis [35,36], the moderate steatosis induced by a short-time hypothyroidism in female rabbits allows the regeneration of the liver.…”
Section: Discussioncontrasting
confidence: 58%
“…For the experiment, control (n = 6) and hypothyroid (Hypo; n = 6) rabbits were daily provided with pellet food and tap water ad libitum during one month. The hypothyroidism was induced by a treatment with 0.02 % methimazole (MMI; approximate diary dosage of 10 mg/kg, Sigma) in the drinking water [19,20]. The Guidelines of Mexican Law of Production, Care and Use Laboratory Animals (NOM-062-ZOO-1999) were followed throughout the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the study of mechanisms, an in vivo study demonstrated that methimazole-induced hypothyroidism promotes immune cell infiltration into pancreatic islets of female rabbits, which could be inducing pancreatitis and insulitis [ 79 ]. Other mechanisms involved in islet dysfunction may be related to different signals.…”
Section: Roles Of Thyroid and Thyroid Hormone In Pancreas Pathogenmentioning
confidence: 99%
“…In patients with hypothyroidism, violations of exocrine and endocrine functions of the pancreas are often revealed. The relationship of the pancreas with the thyroid gland is not completely disclosed; although the structural and functional features of the insular apparatus of the pancreas under hypothyroidism are described in the literature in details [12][13][14], the peculiarities of pancreatic lesions in hypothyroidism remain insufficiently studied.…”
Section: Introductionmentioning
confidence: 99%